Pengaruh Metode Pembelajaran Example Non Example Terhadap Kemampuan Menulis Teks Eksposisi Siswa Kelas X SMAN 1 Lembah Gumanti - Yusrita, Sisi Yusrita; Yulianti Dn, Upit; Gemarni Tatalia, Ricci (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2023)
This study aims to describe the Effect of the Example Non Example Method on Learning to Write Exposition Text for Class X Students of SMA N 1 Gumanti Valley. This type of research is quantitative research with experimental methods. The population of this study is grade X students of SMA N 1 Lembah Gumanti who are enrolled in the 2022/2023 school year totaling 256 students. The sample of this study was students of class XE6 as a control class and XE7 as an experimental class. The data in this study is the performance score of the ability to write exposition text for grade X students of SMA N 1 Gumanti Valley without and using the Example Non Example Method. The results of this study based on data analysis are that there is a significant influence of the use of the example non example method on the ability to write exposition texts for grade X students of SMA N 1 Gumanti Valley because the tcount > ttable (6.48>1.67), so that H0 is rejected and H1 is accepted.